Russian logics and the culture of impossible: Part II: Reinterpreting algorithmic rationality - TATARCHENKO, Ksenia (Institutional Knowledge at Singapore Management University, 2022)
This article reinterprets algorithmic rationality by looking at the interaction between mathematical logic, mechanized reasoning, and, later, computing in the Russian Imperial and Soviet contexts to offer a history of the algorithm as a mathematical object bridging the inner and outer worlds, a humanistic vision that we, following logician Vladimir Uspensky, call the “culture of the impossible.” We unfold the deep roots of this vision as embodied in scientific intelligentsia. In Part I, we examine continuities between the turn-of-the-twentieth-century discussions of poznaniye—an epistemic orientation towards the process of knowledge acquisition—and the postwar rise of the Soviet school of mathematical logic. Establishing this connection allows us to explain, in Part II, the role of the algorithm in disciplinary dynamics between mathematical logic and cybernetics and a characteristic understanding of programming, not as a narrow skill, but as a matter of consciousness.